Analysis of surface crack using various crack growth models - Mohd Akramin, Mohd Romlay (IOP Publishing, 2020)
This research focusing on fatigue crack growth experiment and assessments of fatigue crack growth model. Fatigue has been considered as the most important phenomena in the engineering problems. It has been found to occur in every engineering field. Many methods were introduced to overcome fatigue problem. One of it is fatigue crack growth prediction models. Fatigue crack growth model prediction can determine the residual life of the mechanical component. Fatigue crack growth is an important parameter in engineering. It may begin from undamaged area and propagate afterwards. In this case, a mechanical component condition before an unstable crack still can be used until fatigue. With the study of fatigue crack growth, it can predict the crack life of the component and can reduce cost to repair the component. In this thesis, primary objective is to develop, test and provide computational fracture mechanics model that emphasized an uncertainties quantification for surface crack. Fracture and failure study that has been promoted by S-version finite element method is focus on the analysis of the surface-crack problem. In this project, a few limitations of the study have been implemented as to present a specific scope of the investigation. Both fatigue crack growth model is considered; Paris law model and modified Forman model. The specimen in this analysis is aluminium al 2024 T3. The effect of load on the fatigue crack growth rate is investigated on aluminium 2024 T3. It is concluded that modified Forman has a low exponent compared to the Paris law. Further the crack growth prediction based on modified Forman is lower than Paris law. Paris law only can predict the crack in the region II while modified Forman can predict the crack in region II and III. After finish setup the project based on the instruction, the project is proceeded and the data is collected. The result is analysed based on the objective by using data collected from the project. After that, conclusion is made based on the result of the project.